Analysis of training and performance characteristics during the season 19/20 in comparison to the season 20/21 with Covid-19 restrictions - Kock, H.; Hanstock, H.; Schürer, A. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Aim To describe the training characteristics of German cross-country skiers across two seasons and investigate the effects of Covid-19 restrictions -on training characteristics during lockdowns, as well as on laboratory test- and racing performance in the 2020/21 competition season compared to 2019/20.